Implementasi Manajemen Kinerja Dalam Meningkatkan Efektivitas Pelayanan Publik Dikantor Desa Hutagodang Kec. Sungai Kanan Kabupaten Labuhanbatu Selatan Sumatera Utara - Deni Irawan; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of effective performance management in increasing productivity and motivation in government agencies. In particular, the implementation of performance management at the Hutagodang Village Office, Sungai Kanan District, South Labuhanbatu Regency, North Sumatra is a strategic step to increase the effectiveness of employee work and public services. This study aims to analyze the performance management system implemented, as well as the factors that affect its success. Drawing on regulatory frameworks such as the Government Agency Performance Accountability System (SAKIP), the study highlights the importance of clear performance planning, systematic measurement and evaluation, and a supportive organizational culture.However, challenges such as lack of internal communication, limited human resources, and problems with facilities and infrastructure are still obstacles in the implementation of this system. The results of the study show that improvement efforts in these aspects can significantly improve employee performance, thereby contributing to improving the quality of public services at the Hutagodang Village Office, Sungai Kanan District, South Labuhanbatu Regency, North Sumatra Thus, effective performance management can be an important tool in achieving better government goals and being responsive to the needs of the community.